Analisis Pengaruh Rasio Likuiditas, Rasio Leverage Dan Aktivitas Terhadap Profitabilitas Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Dibursa Efek Indonesia (Bei) - B11110013, Eka Rahayu (Jurnal Manajemen Update, 2015)
Purpose of this research for know the influence of liquidity, leverage and activity to profitability in partial or simultaneous manner. Population in this research is company of drink and foot that enrolled in Bursa Efek Indomesia during 2009-2012. Sample that is thoroughed as much 10 company with purposive sampling manner. Variable tha is thoroughed is liquidity (current ratio), leverage (debt to total assets), activity (total assets turn over) and profitability(retrun on asset) as variable connection. Data that is used data’s secondary and analized used doubled regression linier( test t, test f, correlation pearson and coeffecient,determination) with through assumption classic test that contain normalization test, linieritas, heterokedatisitas,autokorelasi dan multikolinearitas, with use aid program of SPSS version 16.00. Result of research point out variable leverage (debt to total assets) in partial significant to profitabilitas (retrun on asset) company food and drink that enrolled in BEI period 2009-2012. While variable liquidity (current ratio) dan activity (total assets turn over) poin out are not significant to profitability (retrun on asset). Key word : Liquidity (current ratio), Leverage (debt to total assets), Activity (total assets turn over), and profitability (retrun on asset)